2017
DOI: 10.1016/j.jbi.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

A new method of content based medical image retrieval and its applications to CT imaging sign retrieval

Abstract: This paper proposes a new method of content based medical image retrieval through considering fused, context-sensitive similarity. Firstly, we fuse the semantic and visual similarities between the query image and each image in the database as their pairwise similarities. Then, we construct a weighted graph whose nodes represent the images and edges measure their pairwise similarities. By using the shortest path algorithm over the weighted graph, we obtain a new similarity measure, context-sensitive similarity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 23 publications
0
37
0
3
Order By: Relevance
“…Recently, pulse coupled neural network and non-subsampled contourlet transform based CBMIR method is introduced by Kundu et al [26] . Ma et al [27] propose a new CBMIR method know as fused context-sensitive similarity (FCSS) based on support vector machine (SVM) and several distance measures. vector quantization with fuzzy signatures is used in [28] to develop a new system called fuzzy medical image retrieval (FMIR).…”
Section: Review On Existing Methodsmentioning
confidence: 99%
“…Recently, pulse coupled neural network and non-subsampled contourlet transform based CBMIR method is introduced by Kundu et al [26] . Ma et al [27] propose a new CBMIR method know as fused context-sensitive similarity (FCSS) based on support vector machine (SVM) and several distance measures. vector quantization with fuzzy signatures is used in [28] to develop a new system called fuzzy medical image retrieval (FMIR).…”
Section: Review On Existing Methodsmentioning
confidence: 99%
“…Ma, L., Liu, X. [9] proposed the Fused Context-Sensitive Similarity based on Content based Medical Image retrieval focusing specifically on CT images especially for Lung related diseases [9]. This was done based on similarity between visual feature and classification information from the LISS dataset images.…”
Section: Related Workmentioning
confidence: 99%
“…A multi-tiered imaa ge retrieval system foo r microscopic imaa ges is presented by Akakin et al, in [15]. Lan et al, [16] [17] for lung CT image rett rieval which uses the shortest pat th algorithm over thee weighted graph to o measure the both semantic and visual similarities. Image retrieval systee m for heterogeneoo us medical images is proposed ii n [18] by combining the color autocorrelogram, micro-textures and enhanced edge orientation autocorrelogram features, computed using a framewor rk based on Fulll range Autoregressive modd el and it is reported that it is superior in efficiency because of comprising color, texture, shape and its spatial information at both local ann d global level.…”
Section: Introductionmentioning
confidence: 99%